2018
DOI: 10.30802/aalas-cm-17-000126
|View full text |Cite
|
Sign up to set email alerts
|

Crossmatching Maternal and Fetal Blood in Sheep

Abstract: We investigated the incidence of ex vivo incompatibility between ovine maternal RBC and fetal plasma. Time-mated singleton pregnant ewes (n = 8) underwent cesarean delivery of the fetus; at the time of delivery, paired maternal and fetal blood samples were collected and subsequently separated for storage as packed RBC and fresh frozen plasma. Gel column crossmatching was performed 3 to 4 wk later. All fetus-dam crossmatches were considered major crossmatches, combining fetal (recipient) plasma with dam (donor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A score of 1+ was given if RBCs were seen in the bottom half of the gel, 2+ if RBCs were seen throughout the entire gel, 3+ if RBCs were seen in the top half of the gel, and 4+ if all RBCs were evident in a tight disc at the top of the gel. Consistent with literature in dogs 2 and with our previous study, 7 crossmatches were interpreted as compatible or negative, if less than or equal to 1+, and incompatible or positive if greater than or equal to 2+. Compatibility reactions were evaluated by a single experienced investigator (CRS).…”
supporting
confidence: 83%
See 4 more Smart Citations
“…A score of 1+ was given if RBCs were seen in the bottom half of the gel, 2+ if RBCs were seen throughout the entire gel, 3+ if RBCs were seen in the top half of the gel, and 4+ if all RBCs were evident in a tight disc at the top of the gel. Consistent with literature in dogs 2 and with our previous study, 7 crossmatches were interpreted as compatible or negative, if less than or equal to 1+, and incompatible or positive if greater than or equal to 2+. Compatibility reactions were evaluated by a single experienced investigator (CRS).…”
supporting
confidence: 83%
“…The incidence of incompatibility reactions between dams in this study was low as compared with previous studies, which reported a frequency of incompatibility from 16% to 30.8%. 4,7,10 The size and structure of these studies varied, with 12 male Merino sheep in a prospective study, 10 58 small ruminants in a retrospective clinical case series 4 and 8 Merino ewes in the most recent prospective study. 7 This variation in sample size, breed of sheep and methodology complicates meaningful comparison the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations